SNAPflex: a paper-and-plastic device for instrument-free RNA and DNA extraction from whole blood. Issue 18 (7th August 2020) - Kolluri, Nikunja; Albarran, Nikolas; Fan, Andy; Olson, Alex; Sagar, Manish; Young, Anna; Gomez-Marquez, José; Klapperich, Catherine M.
Abstract : Nucleic acid amplification tests (NAATs), which amplify and detect pathogen nucleic acids, are vital methods to diagnose diseases, particularly in cases where patients exhibit low levels of infection. Abstract : Nucleic acid amplification tests (NAATs), which amplify and detect pathogen nucleic acids, are vital methods to diagnose diseases, particularly in cases where patients exhibit low levels of infection. For many blood-borne pathogens such as HIV or Plasmodium falciparum, it is necessary to first extract pathogen RNA or DNA from patient blood prior to NAAT analysis. Traditional nucleic acid extraction methods are expensive, resource-intensive and are often difficult to deploy to resource-limited areas where many blood-borne infections are widespread. Here, we describe a portable, paper-and-plastic device, called SNAPflex, for instrument-free nucleic acid extraction from whole blood, which builds upon our previous work for RNA extraction using a pressure-driven extraction system. SNAPflex shows improved HIV RNA extraction from simulated patient samples compared to traditional extraction methods as well as long-term stability of extracted RNA without the need for cold storage. We further demonstrated successful extraction and recovery of P. falciparum DNA from cultured parasites in whole blood. SNAPflex was designed to be easily manufacturable and deployable to resource-limited settings.